2022
DOI: 10.1002/joc.7789
|View full text |Cite
|
Sign up to set email alerts
|

Changing temporal volatility of precipitation extremes due to global warming

Abstract: It is of utmost importance to understand how precipitation extremes change due to global warming. Here, we examine the volatility of precipitation extremes by analysing the waiting time distribution between events and the clustering of precipitation extremes. For this we use the ERA5 reanalysis data and high-resolution simulations with the Community Earth System Model (CESM). We find significant evidence for a power-law distribution of waiting times between precipitation extremes and of serial clustering of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…They also observed that heavy rainfall days exhibited a decrease before 2013, and the decreasing trend was alleviated after 2013. Given the spatiotemporal variability of mean and extreme precipitation climatology, several studies have analyzed the reasons for the observed differences [21][22][23][24][25], including geographical factors [26][27][28][29], global warming [30][31][32], circulation factors [11,[33][34][35][36], and urbanization [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that heavy rainfall days exhibited a decrease before 2013, and the decreasing trend was alleviated after 2013. Given the spatiotemporal variability of mean and extreme precipitation climatology, several studies have analyzed the reasons for the observed differences [21][22][23][24][25], including geographical factors [26][27][28][29], global warming [30][31][32], circulation factors [11,[33][34][35][36], and urbanization [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated precipitation extremes at global and regional scales from sub‐hour to interannual time scales (Barton et al, 2022; Delgado‐Torres et al, 2023; Dhakal et al, 2023; Jong et al, 2023; Meng et al, 2023; Qin, 2022; Wang et al, 2022), including their connections with the surface air temperature in the Clausius–Clapeyron relationship (Franzke, 2022; Giorgi & Ciarlo, 2022; O'Gorman & Schneider, 2009; Qin et al, 2021; Qin & Shi, 2022; Thackeray et al, 2022), large‐scale atmospheric circulation (Barton et al, 2022; Dhakal et al, 2023) and oceans (Liu, Gao, et al, 2021; Wei et al, 2021). Due to the high internal variability, low spatial resolution and limited temporal length of observations as well as the large uncertainty in model simulations, it is still challenging to study changes in precipitation extremes and their underlying mechanisms in low signal‐to‐noise ratio systems (de Vries et al, 2023; Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%